Coexistence of chancroid and donovanosis in HIV with low CD4 count: a rare case - ., Ravikanti; R., Sunitha B.; ., Vishwanath; B, Murugesh (International Journal of Research in Medical Sciences, 2017)
Genital ulceration as a syndrome has been associated with increased transmission of HIV. The purpose of the present study is to establish skin diseases as clinical indicators of underlying immune status and help in clinical monitoring by estimating and correlating with low CD4 count. This study concludes that, cutaneous manifestations can be considered as good clinical indicators to predict and assess the underlying immune status and reviews the need to be aware of this entity.